Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Foundations and Frontiers of Ecosystem Science: Legacy of a Classic Paper (Odum 1969) - Jessica R. Corman; Scott L. Collins; Elizabeth M. Cook; Xiaoli Dong; Laureano A. Gherardi; Nancy B. Grimm; Rebecca L. Hale; Tao Lin; Jorge Ramos; Lara G. Reichmann; Osvaldo E. Sala (Ecosystems, 2019)

Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Jennifer Lin; Robert Y. L. Zee; Kuang-Yu Liu; Shumin M. Zhang; I-Min Lee; JoAnn E. Manson; Edward Giovannucci; Julie E. Buring; Nancy R. Cook (Cancer Causes & Control, 2010)

Physical activity, adiposity, and risk of endometrial cancer - Molly B. Conroy; Jacob R. Sattelmair; Nancy R. Cook; JoAnn E. Manson; Julie E. Buring; I-Min Lee (Cancer Causes & Control, 2009)

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Interaction between inflammation-related gene polymorphisms and cigarette smoking on the risk of myocardial infarction in the Physician’s Health Study - Sarah A. Rosner; Paul M. Ridker; Robert Y. L. Zee; Nancy R. Cook (Human Genetics, 2005)

Dietary intakes of fruit, vegetables, and fiber, and risk of colorectal cancer in a prospective cohort of women (United States) - Jennifer Lin; Shumin M. Zhang; Nancy R. Cook; Kathryn M. Rexrode; Simin Liu; JoAnn E. Manson; I-Min Lee; Julie E. Buring (Cancer Causes & Control, 2005)

TP53 haplotype-based analysis and incidence of post-angioplasty restenosis - Robert Y. L. Zee; Nancy R. Cook; Chung-Ah Kim; Arturo Fernandez-Cruz; Klaus Lindpaintner (Human Genetics, 2004)

Body Mass Index and Risk of Colorectal Cancer in Women (United States) - Jennifer Lin; Shumin M. Zhang; Nancy R. Cook; Kathryn M. Rexrode; I-Min Lee; Julie E. Buring (Cancer Causes & Control, 2004)

TP53 haplotype-based analysis and incidence of post-angioplasty restenosis - Robert Y. L. Zee; Nancy R. Cook; Chung-Ah Kim; Arturo Fernandez-Cruz; Klaus Lindpaintner (Human Genetics, 2004)

Estrogen–progestin replacement therapy and breast cancer risk: the Women's Health Study (United States) - Juliet V. Porch; I-Min Lee; Nancy R. Cook; Kathryn M. Rexrode; Julie E. Buring (Cancer Causes & Control, 2002)

Physical activity and breast cancer risk: the Women's Health Study (United States) - I-Min Lee; Kathryn M. Rexrode; Nancy R. Cook; Charles H. Hennekens; Julie E. Buring (Cancer Causes & Control, 2001)

Effects of beta-carotene supplementation on cancer incidence by baseline characteristics in the Physicians' Health Study (United States) - Nancy R. Cook; I-Min Lee; JoAnn E. Manson; Julie E. Buring; Charles H. Hennekens (Cancer Causes & Control, 2000)

Adult height and incidence of cancer in male physicians (United States) - Patricia R. Hebert; Umed Ajani; Nancy R. Cook; I-Min Lee; Ki Sau Chan; Charles H. Hennekens (Cancer Causes & Control, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)